Analisis Mekanisme Pembayaran Pajak Kendaraan Bermotor di Kantor Sistem Administrasi Manunggal Satu Atap Kecamatan Kuantan Tengah - Elfi Rahmita Sari; Sarjan M; Emilia Emharis; Rika Ramadhanti; Shilvirichiyanti Shilvirichiyanti (Departement of Mathematics Education, 2024)
Currently, the administrative procedures for tax collection at the SAMSAT office, most people do not know the mechanism for tax collection carried out by officers. So based on this, the author is interested in researching